PERBANDINGAN KELENGKAPAN PENGISIAN REKAM MEDIS KONVENSIONAL DAN PROTOTIPE INTEGRATED ELECTRONIC SURGICAL REPORT (IESR) - Nyoman Dwi Maha Udiyana; Ede Surya Darmawan; Cicilya Candi (Coping: Community of Publishing in Nursing, 2021)
The utilisation of Electronic Medical Record (EMR) is an implementation of information and communication technological development in healthcare. EMR improve quality and documentation of medical record. Integrated Electronic Surgical Report (IESR) prototype is an EMR development that concerned on surgical report fulfillment, allows the surgeon fullfill an android based medical record efficiently. This research is mixed method study, using qualitative study to get feedback from the IESR user, and a cross sectional analytic study to know the comparison of medical records filling completeness between Integrated Electronic Surgical Report (IESR) and conventional medical records at Sultan Imanuddin hospital. Secondary data of 31 medical record sample from medical record department in october until december 2020 was obtained. Bivariate analysis result using Mann_Whitney test showed p=0.061. There are few positive aspect including: simplicity , short duration and efficiency in medical record fulfilment using IESR. But there is no significant difference between IESR prototype utilisation and conventional medical record in term completeness fulfilment of surgical ward patients medical record.